2021
DOI: 10.1021/acs.bioconjchem.1c00014
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Chitosan Engineered Scaffolds for Biomedical Applications

Abstract: Peptides are signaling epitopes that control many vital biological events. Increased specificity, synthetic feasibility with concomitant lack of toxicity, and immunogenicity make this emerging class of biomolecules suitable for different applications including therapeutics, diagnostics, and biomedical engineering. Further, chitosan, a naturally occurring linear polymer composed of D-glucosamine and N-acetyl-D-glucosamine units, possesses anti-microbial, muco-adhesive, and hemostatic properties along with excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 177 publications
0
17
0
Order By: Relevance
“…Chitosan-polymer materials display amphiphilic behavior that dispenses in organic solvents and could be utilized in multiple medical applications like engineering tissues and bone reconstruction [111]. Peptide chitosan hybrids have biosignaling properties and cell adhesion properties that could be utilized for drug delivery, cell therapy, and engineering tissues.…”
Section: Role In Biomedical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan-polymer materials display amphiphilic behavior that dispenses in organic solvents and could be utilized in multiple medical applications like engineering tissues and bone reconstruction [111]. Peptide chitosan hybrids have biosignaling properties and cell adhesion properties that could be utilized for drug delivery, cell therapy, and engineering tissues.…”
Section: Role In Biomedical Applicationmentioning
confidence: 99%
“…It preserves the purity of the finished matrix as no catalyst or initiators are added to the solid-state reactive blend. These polymeric materials find multiple applications in the biomedical field [111].…”
Section: Role In Biomedical Applicationmentioning
confidence: 99%
“…Plant derived proteins and polysaccharides have proved to be more sustainable and less expensive than their animal counterpart, overcoming some issues in extraction and source recovery 37 . However, stable and water-resistant scaffolds can be obtained only after crosslinking or blending steps 38 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Natural polymers such as chitosan polysaccharides, composed of β-(1 4)-linked D-glucosamine and N -acetyl-D-glucosamine units, have been used extensively as a nanocarrier for oral peptide delivery [ 28 ]. Chitosan-based NPs exhibited excellent biocompatibility and gastrointestinal (GI) absorption and have been used to deliver anticancer agents [ 29 , 30 ]. With respect to therapeutic peptide delivery, Kanwar et al demonstrated that lactoferrin polypeptide-loaded chitosan NPs can effectively activate apoptotic pathways in colon cancer and cancer stem cells [ 31 ].…”
Section: Peptide Modifications For Enhanced Delivery and Stabilitymentioning
confidence: 99%